Long-term effectiveness and treatment timing for bionator therapy - Faltin, K.; Faltin, R. M.; Baccetti, T.; Franchi, L.; Ghiozzi, B.; McNamara, J. A. (E H Angle Education Research Foundation, Inc, 2003)
The aim of the present investigation was to provide information about the long-term effects and optimal timing for class-II treatment with the Bionator appliance. Lateral cephalograms of 23 class-II patients treated with the Bionator were analyzed at three time periods: T1, start of treatment; T2, end of Bionator therapy; and T3, long-term observation (after completion of growth). T3 includes a phase with fixed appliances. The treated sample was divided into two groups according to their skeletal maturity as evaluated by the cervical vertebral maturation (CVM) method. The early-treated group (13 subjects) initiated treatment before the peak in mandibular growth, which occurred after completion of Bionator therapy. The late-treated group (10 subjects) received Bionator treatment during the peak. The T1-T2, T2-T3, and T1-T3 changes in the treated groups were compared with changes in control groups of untreated class-II subjects by nonparametric statistics (P < .05). The findings of the present study on Bionator therapy followed by fixed appliances indicate that this treatment protocol is more effective and stable when it is performed during the pubertal growth spurt. Optimal timing to start treatment with the Bionator is when a concavity appears at the lower borders of the second and the third cervical vertebrae (CVMS 11). In the long term, the amount of significant supplementary elongation of the mandible in subjects treated during the pubertal peak is 5.1 mm more than in the controls, and it is associated with a backward direction of condylar growth. Significant increments in mandibular ramus height also were recorded.
Keywords: class-II malocclusion; functional jaw orthopedics; cephalometrics; cervical vertebral maturation